2015
DOI: 10.1128/aac.01292-15
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Qnr on Agents Other than Quinolones That Target DNA Gyrase

Abstract: bQnr is a plasmid-encoded and chromosomally determined protein that protects DNA gyrase and topoisomerase IV from inhibition by quinolones. Despite its prevalence worldwide and existence prior to the discovery of quinolones, its native function is not known. Other synthetic compounds and natural products also target bacterial topoisomerases. A number were studied as molecular probes to gain insight into how Qnr acts. Qnr blocked inhibition by synthetic compounds with somewhat quinolone-like structure that targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…Based on the results gotten from this study, all the selected compounds are considered as specific ligand of DNA gyrase with high docking scores (Figure 3), hence they possess antimicrobial properties. This is in agreement with reported results of previous studies [6,23,24].…”
Section: Resultssupporting
confidence: 94%
“…Based on the results gotten from this study, all the selected compounds are considered as specific ligand of DNA gyrase with high docking scores (Figure 3), hence they possess antimicrobial properties. This is in agreement with reported results of previous studies [6,23,24].…”
Section: Resultssupporting
confidence: 94%
“…Many naturally occurring antibiotics and synthetic agents also target DNA gyrase. Qnr protects against compounds with a somewhat quinolone-like structure (Jacoby et al 2015), for example, 2-pyridone (Flamm et al 1995), quinazoline-2,4-dione (Huband et al 2007), or spiropyrimidinetrione (Kern et al 2011), so it is not strictly quinolone-specific. Qnr, however, does not block agents acting on the GyrB subunit, and it also does not block simocyclinone D8, which, like quinolones, binds to the amino terminus of GyrA and blocks DNA binding (Hearnshaw et al 2014).…”
Section: Qnr Structure and Functionmentioning
confidence: 99%
“…It was observed that Qnr also confers slight protection against 2-pyridones, quinazoline-2,4-diones (both of which are structurally closely related to quinolones), and spiropyrimidinetriones but has no protective effect against other topoisomerase type II-targeting molecules such as aminocoumarins (coumermycin A1, novobiocin, and simocyclinone D8), gyramide A, microcin B17, pyrazolopyridones, or tricyclic pyrimidoindoles (310).…”
Section: Qnrmentioning
confidence: 99%